Employee and Organizational Impacts of Flexitime Work Arrangements - Eldridge, Derek; Nisar, Tahir (Relations industrielles / Industrial Relations, 2011)
There is evidence of heavy job demands and low control resulting in multiple negative consequences for employees and their families. Understandably, there is then a desire to move away from such practices and adopt more flexible organizational systems. In such environments, employees may be more in control of their workloads, and manage a better balance between life and work. Flexitime provides increased opportunity to fit other commitments and activities in with work, and make better use of their free time. As employees can choose their own start and finish times for the working day, they can take a little extra time off in a week. It is argued that creating such opportunities improve motivation and raises morale. This also allows for lower stress in the work place and greater enjoyment in the home. Consequently, employees experience increased performance in the work place and greater repertoire for marketing to new employers. Using WERS (The British Workplace Employee Relations Survey), the present study examines the nature of such relationships, and specifi cally explores the usage of flexitime and employee and organizational outcomes. WERS provides a useful set of information about work environment, job characteristics, and occupation, permitting researchers to conduct a more detailed analysis of individual employee behaviour. We develop our hypotheses based on the organizational behaviour literature that is concerned with exploring the nature of individual and organizational responses in challenging and stressful environments. Our results show a negative relationship between flexitime and job security. There is also no evidence of establishments with flexitime work arrangements having less stressed employees. Flexitime may however lead to increased employee participation in decision making as measured by employee discretion and team work. Our fi ndings thus stress the need to be cautious about how we build the case for the adoption of flexitime.